Di Bawah Payung Habib: Sejarah, Ritual, Dan Politik Tarekat Syattariyah Di Pantai Barat Aceh - Sehat Ihsan Shadiqin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
This article looks at the development of Sufism in the form of Sufi orders (tarekat) in contemporary Aceh, notably Syattariah order (Tarekat Syattariyah). Syattariah order has a strong foundation in the history of Islam in Aceh. A great Acehnese scholar, Abdurrauf As-Singkili is the figure who spread this order in the archipelago. One of the centers of the development of the Syattariyah order in contemporary Aceh is Nagan Raya with Habib Muda Seunagan as the main leader. Syattariah grows rapidly under his influence by forming a special formula that is very preferential to the local culture. His role is evident in the term "join under Habib's umbrellaâ€ held by his congregation. However, the new development of the Syattariyah order also raises some accusations against its practice, as it is considered contrary to the teachings of Islam in general. Accusation of being a heresy and contrary to Islam, as "Salek Buta" not infrequently addressed. I conducted observations, interviews and obtained various documents related to the research. I have come to the conclusion that the Syattariah order in Nagan Raya has grown according to what they believe and practice. Congregations believe that the allegations conveyed are incompatible with reality and do not represent what they think. The Syattariyah order persists due to the strong support of family networks, the great role in the formation of indigenous peoples, and the political role in government played by the elite